Estudo da solvência atuarial, econômica e financeira dos regimes próprios de previdência social municipais cearenses - Silva, Francisco Wilson Ferreira da (2014)
The Brazilian legal system , starting from 1998 revealed that the federative states and municipalities could migrate from the General Provident Fund Scheme ( RGPS ) , headed by the INSS , for its Own Social Security System ( RPPS ) taking care to financial contributions necessary for the harmony of actuarial balance to ensure in the future payment of benefits to those eligible ( work force included in pension schemes ) , so that the 5,509 Brazilian municipalities, 1,957 have instituted their RPPS and 55 towns in State of Ceará , the existing 184 . The main objective of this research was to determine the actuarial results of RPPS established in municipalities of Ceará through a software built by the author and confront him with the actuarial results contained in the statements of income of the Actuarial Reviews - DRRA 's. According to the calculations the Ceará municipal RPPS present actuarial deficit in the amount of R $ 3,361,632,976.77 , while the value of actuarial results demonstrated in the present DRAA 's actuarial deficit of R $ 10,344,705,187.76 . In both calculations the deficit result has concentration in the cities of Fortaleza, Canindé, Maracanaú, Juazeiro and Itapipoca. In 1.ª & 2.ª calculating the municipalities of Amontada and Caucaia proved surplus, also adding to the towns of Cruz and Fortim, the surplus calculation performed by the author. The actuarial deficit of the municipality of Itapipoca presented itself takes both the calculation made by the author, as in shown in the DRRA one. It is concluded that the pension deficit loved not offer structural system for the accumulation of resources for the payment of obligations defined benefit plans. There is evidence that there is no consistency in the figures to the MPAS during transport of the DRAA 's MPAS is recommending the external control bodies investigate that the reason pointed out the differences.